Degree of Physical Activity in University Teachers Before and During the COVID-19 Pandemic - Ramírez Enríquez, Silvia Isela; Barrón Luján, Juan Cristóbal; López Baca, Leopoldo Refugio; López Rodríguez, Luis Alberto; Sambrano, Gilberto Santos; Gill, Alicia Rodríguez (European Scientific Journal, ESJ, 2023)
The objective of this work was to analyze the degree of physical activity of university teachers before and during the Covid-19 pandemic, this in the context of social isolation. The present study adopts a quantitative and cross-sectional approach. The sample was determined randomly, made up of 129 university professors from the Faculty of Physical Culture Sciences of the Autonomous University of Chihuahua, aged between 18 and 74 years. The results show that 50.39% of teachers before the pandemic maintained a high degree of physical activity, while during confinement they presented a lower degree of physical activity, decreasing to only 39.53%. The Covid-19 not only wreaked havoc on health, but also negative effects in the psychological, emotional and social sphere of people, as well as havoc in the practice of physical activity, modifying healthy lifestyles and leaving possible effects for the consequent physical health.